VIMO APPLICATIONS AS VIRTUAL MOUSE WITH REAL TIME GESTURE RECOGNITION - Anisa Lora dan Pipit Dewi Arnesia (Prosiding Seminar SeNTIK, 2020)
VIMO APPLICATIONS AS VIRTUAL MOUSE WITH REAL TIME GESTURE RECOGNITION